2020
DOI: 10.1111/nph.16342
|View full text |Cite
|
Sign up to set email alerts
|

Progressive refinement of the karyotyping of Brachypodium genomes

Abstract: Summary Brachypodium distachyon is a weedy grass species that is firmly established as a model for the comparative and functional genomics of temperate cereals and grasses. Its simple, nuclear genome of five chromosomes contrasts it with other relatives of the genus with different, and usually higher, basic chromosome numbers and ploidy levels. This variation in karyotypic structure affords the possibility of reconstructing evolutionary pathways that have shaped the genome structure of extant species. This Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Established as an important model for functional genomics, the small genome of B. distachyon (272 Mb; 30% of TEs) is fully sequenced and assembled into five chromosomes ( International Brachypodium Consortium 2010 ). Comparative genomics and cytogenetic analyses ( Hasterok et al. 2019 ) showed that it underwent multiple and independent nested chromosome fusions which resulted in a higher gene density at the former distal regions of the inserted chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Established as an important model for functional genomics, the small genome of B. distachyon (272 Mb; 30% of TEs) is fully sequenced and assembled into five chromosomes ( International Brachypodium Consortium 2010 ). Comparative genomics and cytogenetic analyses ( Hasterok et al. 2019 ) showed that it underwent multiple and independent nested chromosome fusions which resulted in a higher gene density at the former distal regions of the inserted chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Together with phylogenomics, this approach identified some putative segmental allopolyploids and orphan genomes of some likely extinct ancestors in Brachypodium [41]. Although many kinds of DNA sequences make useful FISH probes [42], CP is particularly informative due to its high specificity (Figure 2A,B). The recent advent of singlecopy oligonucleotides as probes (oligo-FISH) [43] made CP technically feasible in more plants, enabling comparative analyses not only of those with small genomes, like rice [44] but, to some…”
Section: Brachypodium To Study Plant Genome Organisation At the Cytom...mentioning
confidence: 99%
“…porphyrocoma , although these two species belong to different genera. A similar chromosome composition ( x = 10 + 5) was found in polyploidy Brachypodium species, and it was proposed that the x = 10 + 5 species was the hybrid of the x = 10 and x = 5 species (Hasterok et al ., 2020). It is possible that both N .…”
Section: Discussionmentioning
confidence: 99%